Fermi large area telescope observations of the cosmic-ray induced gamma-ray emission of the Earth's atmosphere - Abdo, A. A.; Ackermann, Markus; Ajello, M.; Atwood, W. B.; Baldini, Luca; Ballet, J.; Barbiellini, G.; Bastieri, Denis; Baughman, B. M.; Bechtol, K.; Bellazzini, R.; Berenji, Bijan; et al. (Physical Review D, 2009)
We report on measurements of the cosmic-ray induced gamma-ray emission of Earth's atmosphere by the Large Area Telescope on board the Fermi Gamma-ray Space Telescope. The Large Area Telescope has observed the Earth during its commissioning phase and with a dedicated Earth limb following observation in September 2008. These measurements yielded similar to 6.4x10(6) photons with energies > 100 MeV and similar to 250 hours total live time for the highest quality data selection. This allows the study of the spatial and spectral distributions of these photons with unprecedented detail. The spectrum of the emission-often referred to as Earth albedo gamma-ray emission-has a power-law shape up to 500 GeV with spectral index Gamma=2.79 +/- 0.06.
CRIS-Team WoS Importer:2020-01-15